2014
DOI: 10.3329/bmrcb.v39i2.19643
|View full text |Cite
|
Sign up to set email alerts
|

Photo-anthropometric study on face among Garo adult females of Bangladesh

Abstract: Facial anthropometry has well-known implications in health-related fields. Measurement of human face is used in identification of person in Forensic medicine, Plastic surgery, Orthodontics, Archeology, Hairstyle design and examination of the differences between races and ethnicities. Facial anthropometry provides an indication of the variations in facial shape in a specified population. Bangladesh harbours many cultures and people of different races because of the colonial rules of the past regimes. Standards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…After the first round study selection based on titles and abstracts ( κ = 0.97), 308 potentially eligible articles were accessed for full-texts and underwent the second round study selection. Of these, 36 eligible articles [ 21 56 ] ( κ = 0.95) that reported 38 studies were identified.…”
Section: Resultsmentioning
confidence: 99%
“…After the first round study selection based on titles and abstracts ( κ = 0.97), 308 potentially eligible articles were accessed for full-texts and underwent the second round study selection. Of these, 36 eligible articles [ 21 56 ] ( κ = 0.95) that reported 38 studies were identified.…”
Section: Resultsmentioning
confidence: 99%
“…There are present scientific studies where certain anthropometric measurements were made on a face photograph and mean values were assigned. [7][8][9] However, no studies in literature where the sizes of the anatomic structures on the face were compared to personality characteristics could be found.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric measurements provide important values that are needed in orofacial surgery. The normal values of facial parameters are vital measurements in the evaluation and diagnosis of craniofacial deformities 4 .…”
Section: Introductionmentioning
confidence: 99%